PERAN GUBERNUR DALAM PEMBENTUKAN DAERAH OTONOMI BARU (DOB) KABUPATEN/KOTA - Nasrin Nasrin; Darmawan Wiridin; Khairun Hidayat (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
Autonomy is the development of autonomous Indonesian people, which provides flexibility for the optimal formation of the best potentials of each individual. Autonomous individuals become the basic capital for the realization of true regional autonomy. Therefore, the strengthening of regional autonomy must open equal and widest opportunities for every actor according to mutually agreed guidelines as a guarantee for the implementation of social order. This research is explanatory and analytical descriptive in nature, namely research that explores and at the same time provides an overview or description of the Role of the Governor in the Implementation of Regional Autonomy at the Regency/City Level Based on Law Number 23 of 2014 concerning Regional Government, while the method used is the juridical method normative and historical methods. The normative juridical method is used to examine applicable legal principles, while the historical method is used to examine the principles regarding parental responsibility for children after a divorce. This research includes normative legal studies that use normative doctrinal methods, namely rules as teachings that guide behavior. The requirements for forming a New Autonomous Region (DOB) are (1) Basic/Technical Requirements; (2) Administrative Requirements; and (3) Regional Physical Requirements. From a regulatory perspective, it can be seen that there are several roles that can be played by the provincial government in assisting the implementation of regional expansion. The first role that must be carried out is in terms of preparing regional studies. Another role that can be carried out by the provincial government, in this case the governor, in assisting regional expansion is related to the matter of proposals as a follow-up to the aspirations of the community and the regency/main city government. Related to the nature of the Governor's approval for regional expansion are the stages that must be carried out as mandated in PP No. 78 of 2007.